USE OF RITUXIMAB IN PATIENTS WITH LUPUS NEPHRITIS - Anna Vasilyevna Torgashina (Научно-практическая ревматология, 2010)
Objective: To evaluate the impact of rituximab (RTM) therapy on the clinical, morphological, and immunological parameters of lupus nephritis (LN) activity. Subjects and methods. The study included 19 patients with types III and IV LN (WHO classification) with its 6-133-month history. Their mean age was 28,6 years (18-63 years). RTM was given in a dose of 500 mg weekly for 4 weeks or 1000 mg twice at an interval of 2 weeks. Fourteen patients received a complete course of RTM therapy. Five cases could not complete the course due to poor tolerability or death. Renal rebiopsy was performed in 8 patients 6-12 months after therapy initiation. Results. Thirteen patients achieved partial remission in different follow-up periods. Complete remission was noted in 7 patients a year after a course of RTM therapy. There were no exacerbations of LN in remission patients. Just a month after therapy was marked by a decline in the systemic lupus erythematosus disease activity index (SLEDAI 2K) from 20.4+7.3 to 14.3+6.5 (p